Interactions between local people and lakes: An example from Turkey - Alkan, Hasan; Korkmaz, Mehmet; Altunbas, Sevda (Journal of Environmental Engineering and Landscape Management, 2018)
The interaction of rural settlements by the Egirdir Lake and surroundings has been discussed in this study that has been conducted in order to support the studies of the Egirdir Lake Management Plan that is stated as a result of two‐year study and to provide local participation for these studies. The method used in this study is based on questionnaire, interviews, and direct observations. Besides several meetings about rural settlements and the Egirdir Lake were conducted among local people, stakeholders and expert groups. According to the results of this study, the Egirdir Lake surroundings have been an important centre of attraction for human settlements from the past to the present. The people that established settlements around the Lake benefited from the Lake for various purposes. The benefit from the Egirdir Lake had not reached the sizes that could affect the hydrology of the Lake until 1960s. However, start of benefiting from the Lake for the purpose of agricultural irrigation in those years and the variation of benefit in the following years have been a significant element of pressure on the Lake. By reasons of these benefits, the Lake has consistently showed water deficit, and the pollution of the Lake has reached considerable sizes as well. When effectively managed by means of the Lake Management Plan, prepared with a participatory approach, the Lake can be protected from these negative effects. Gyvenvietės ežerų apylinkėse. Naudojimasis ir jiems daroma žala (Turkijos pavyzdys) Santrauka. Nagrinėjamas Egirdir ežero ir jį supančių kaimo gyvenviečių nevienareikšmis ryšys – nauda turima iš ežero ir jam daroma žala. Tyrimas buvo atliekamas dvejus metus kurtam Egirdir ežero tvarkymo planui papildyti. Tyrimo metodas pagrįstas apklausomis, interviu ir tiesioginiais stebėjimais. Buvo organizuota keletas vietinių žmonių, tarpininkų ir ekspertų grupių susitikimų dėl Egirdir ežero tvarkymo. Šio ežero aplinka visada buvo svarbus traukos centras žmonėms įsikurti. Žmonės, apsistoję aplink ežerą, naudojosi juo įvairiais tikslais. Iki 1960 m. tai ežero hidrologijai didesnės įtakos neturėjo. Situacija pablogėjo ežerą pradėjus naudoti žemės naudmenoms drėkinti. Labai suaktyvėjo ir ežero tarša. Efektyviai laikantis planingų tvarkymo priemonių, ežeras gali būti apsaugotas nuo neigiamo poveikio. Reikšminiai žodžiai: Egirdir ežeras, tarša, ežero tvarkymo planas, dalyvavimas, kaimo gyvenvietės, Turkija. Приозерные поселения. Использование озер и наносимый им вред (на примере Tурции) Резюме. Исследуется взаимосвязь сельских поселений вблизи озера Эгирдир и окружающей среды: польза, получаемая от озера, и наносимый ему вред. Исследование дополняет план обустройства озера Эгирдир и предоставляет сведения об участии местных жителей в подобных исследованиях. Метод, применявшийся в исследованиях, основан на опросах людей, интервью и непосредственных наблюдениях. Состоялись встречи местных жителей, посредников и групп экспертов по вопросам заселения поселений и обустройства озера Эгирдир. На основании исследований установлено, что окрестности озера Эгирдир были и остаются важным центром притяжения людей с целью поселиться там. Поселившиеся там люди используют озеро в различных целях. Использование озера Эгирдир до 1960 г. не оказало значительного воздействия на гидрологию озера, однако после того, как озеро стало использоваться для орошения сельскохозяйственных угодий, ситуация ухудшилась. Увеличилась загрязненность озера. Избежать негативного влияния на озеро можно, если эффективно применять меры, предусмотренные планом по обустройству озера. Ключевые слова: озеро Эгирдир, загрязненность, план по обустройству озера, участие, сельские поселения, Турция. First Published Online: 14 Oct 2010